Hyaluronic Acid: Its Versatile Use in Ocular Drug Delivery with a Specific Focus on Hyaluronic Acid-Based Polyelectrolyte Complexes - Saoirse Casey-Power; Richie Ryan; Gautam Behl; Peter McLoughlin; Mark E. Byrne; Laurence Fitzhenry (MDPI AG, 2022)
Extensive research is currently being conducted into novel ocular drug delivery systems (ODDS) that are capable of surpassing the limitations associated with conventional intraocular anterior and posterior segment treatments. Nanoformulations, including those synthesised from the natural, hydrophilic glycosaminoglycan, hyaluronic acid (HA), have gained significant traction due to their enhanced intraocular permeation, longer retention times, high physiological stability, inherent biocompatibility, and biodegradability. However, conventional nanoformulation preparation methods often require large volumes of organic solvent, chemical cross-linkers, and surfactants, which can pose significant toxicity risks. We present a comprehensive, critical review of the use of HA in the field of ophthalmology and ocular drug delivery, with a discussion of the physicochemical and biological properties of HA that render it a suitable excipient for drug delivery to both the anterior and posterior segments of the eye. The pivotal focus of this review is a discussion of the formation of HA-based nanoparticles via polyelectrolyte complexation, a mild method of preparation driven primarily by electrostatic interaction between opposing polyelectrolytes. To the best of our knowledge, despite the growing number of publications centred around the development of HA-based polyelectrolyte complexes (HA-PECs) for ocular drug delivery, no review articles have been published in this area. This review aims to bridge the identified gap in the literature by (1) reviewing recent advances in the area of HA-PECs for anterior and posterior ODD, (2) describing the mechanism and thermodynamics of polyelectrolyte complexation, and (3) critically evaluating the intrinsic and extrinsic formulation parameters that must be considered when designing HA-PECs for ocular application.